The Gods we worship live next door - Realuyo, Bino A. (Pasig City Anvil Publishing, Inc., 2008)
"In Realuyo's landscape of poetry, the ruins and the ruined of the Philippines gather to speak of "memories that arises from simple truths," and prove that what the punished body cannot endure, the soul will ultimately witness, illuminate, and redeem"--Publisher's description.
Filipineza -- Singapore Sunday -- Amsterdam canal -- Night in Dubai -- Azucar -- Sultan Kudarat -- Procession -- Discovery of skin -- 1899 : the forgotten leaf -- Consummatum est -- GI baby -- Pantoum : the comfort woman -- 1942 : the war haiku -- Japayuki -- From a Filipino death march survivor -- Witness -- Glue children -- Queen -- Flower vendor -- Brownout -- Leaning tenement of Taytay -- Because yesterday I jumped out of a plane -- Pepper-eater -- Lunar eclipse -- Find me -- Cycles -- Gods we worship live next door : a poem in eleven parts.
Keywords: Philippine poetry (English).; Poetry -- Collections; Philippines -- Social conditions -- Poetry